The Relationship Between Macroeconomic Variables And Health Indicators In United Nations Member States: 2002-2010 - Mehdi Khakian; Javad Neshani Sadabad; Mohammad Hadian; Hosein Ghaderi; Malihe Ram; Yaser Jouyani (Tehran University of Medical Sciences, 2015)
Background and Aim: In a severely inflationary environment with unemployment, social problems increase and, therefore, high health care expenses are imposed on the society. Materials and Methods: This was a correlational study. Panel data model and EVeiws 6 software were used in this study. The data were collected from the World Bank website. The required pre-tests, including F-Limer and Hauseman tests, were given to check the appropriateness of data and to determine a appropriate model. Following the pre-tests, the results were estimated in the form of a regression model. Results: The results indicated that F-test and t-statistic were significant, and that R2 statistic was high. In the three models, R2 was 99%, 99% and 98%, respectively. Moreover, it can be said that employment is positively related with life expectancy, but negatively related with infant mortality and total fertility rate. Also, inflation is negatively related with life expectancy, but positively related with infant mortality, and total fertility rate. Finally, Gross Domestic Product (GDP) is negatively related with total fertility rate and life expectancy, but has no meaningful relationship with infant mortality (p = 0.31). Conclusion: Employment, inflation and GDP are the variables that have the greatest impact on health indicators. however, life expectancy is more sensitive to explanatory variables.